Electrical Stimulation Degenerated Cochlear Synapses Through Oxidative Stress in Neonatal Cochlear Explants - Liang, Qiong; Shen, Na; Lai, Bin; Xu, Changjian; Sun, Zengjun; Wang, Zhengmin; Li, Shufeng (Frontiers in Neuroscience, 2019)
Neurostimulation devices use electrical stimulation (ES) to substitute, supplement or modulate neural function. However, the impact of ES on their modulating structures is largely unknown. For example, recipients of cochlear implants using electroacoustic stimulation experienced delayed loss of residual hearing over time after ES, even though ES had no impact on the morphology of hair cells. In this study, using a novel model of cochlear explant culture with charge-balanced biphasic ES, we found that ES did not change the quantity and morphology of hair cells but decreased the number of inner hair cell (IHC) synapses and the density of spiral ganglion neuron (SGN) peripheral fibers. Inhibiting calcium influx with voltage-dependent calcium channel(VDCC) blockers attenuated the loss of SGN peripheral fibers and IHC synapses induced by ES. ES increased ROS/RNS in cochlear explants, but the inhibition of calcium influx abolished this effect. Glutathione peroxidase 1 (GPx1) and GPx2 in cochlear explants decreased under ES and ebselen abolished this effect and attenuated the loss of SGN peripheral fibers. This finding demonstrated that ES induced the degeneration of SGN peripheral fibers and IHC synapses in a current intensity- and duration-dependent manner in vitro. Calcium influx resulting in oxidative stress played an important role in this process. Additionally, ebselen might be a potential protector of ES-induced cochlear synaptic degeneration.